2014
DOI: 10.1111/apt.12771
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in survival associated with embolisation of spontaneous portosystemic shunt in patients with recurrent hepatic encephalopathy

Abstract: SUMMARY BackgroundSpontaneous portosystemic shunt (SPSS) is a frequent cause of recurrent hepatic encephalopathy (HE) in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 35 publications
3
68
0
6
Order By: Relevance
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
“…The details and outcomes of the reviewed studies are listed in Table 1 [13,[32][33][34][35][36][37][38].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
See 3 more Smart Citations